PENGARUH MEDIA DOMATH (DOMINO MATHEMATIC) PADA MATERI PECAHANTERHADAP HASIL BELAJAR SISWA KELAS IV SDN 14 KOTO BARU - Fitria Sri Dewi Nurul Yaqin; Eka Filahanasari; Muhammad Subhan (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is motivated by problems that occur in the field such as limited learning media at school, and students do not pay attention to the teacher when explaining, there is a lack of interest and will lead to low student learning outcomes in participating in learning, passive students when given questions by the teacher which will have an impact on the decline in student learning outcomes, cool with themselves and chatting with their peers. The purpose of this study was to determine the results of the influence of Domath (Domino mathematic) media on fraction material on the learning outcomes of grade IV students of SDN 14 Koto Baru. The type of research used is quantitative using experimental research methods. This research used the form of one group pretest-postest design this design uses one group, namely the experimental class. The post-test results showed an increase in student learning outcomes, where from the pre-test average of 59.736 it increased to 77.368 in the post-test results. In addition, there was a change in the number of students who were complete and incomplete. Students who completed the pre-test were 8 students and increased in the posttest to 16 out of 19 students. These results were followed by the acquisition of excellent post-test scores, where the highest score reached 90 and the lowest score was 55. These learning outcomes show the difference between before treatment and after treatment.